Molecular mechanism of selenoprotein P synthesis - Shetty, Sumangala; Copeland, Paul R. (Biochimica et biophysica acta. General subjects, 2018)
Selenoprotein synthesis requires the reinterpretation of a UGA stop codon as one that encodes selenocysteine (Sec), a process that requires a set of dedicated translation factors. Among the mammalian selenoproteins, Selenoprotein P (SELENOP) is unique as it contains a selenocysteine-rich domain that requires multiple Sec incorporation events. In this review we elaborate on new data and current models that provide insight into how SELENOP is made. SELENOP synthesis requires a specific set of factors and conditions. As the key protein required for proper selenium distribution, SELENOP stands out as a lynchpin selenoprotein that is essential for male fertility, proper neurologic function and selenium metabolism. •Selenoprotein synthesis requires the reinterpretation of a UGA stop codon as one that encodes selenocysteine (Sec).•Selenoprotein P (SELENOP) is unique as it contains a selenocysteine-rich domain that requires multiple Sec incorporation events.•SELENOP synthesis requires a unique set of factors and RNA structures.•SELENOP is essential for male fertility, proper neurologic function and selenium metabolism.